2004
DOI: 10.3354/meps279003
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and viral abundance in Ross Sea summer pack ice communities

Abstract: Abundance of single, non-attached bacteria and viruses <110 nm (likely to have infected bacteria) were determined for surface, interior and bottom ice microhabitats between 66 and 75°S in the Ross Sea during the austral summer of 1999. Emphasis was on sites of ice algal blooms, and bacterial abundance was examined with respect to physical characteristics, chlorophyll a, phaeophytin and, in particular, microbial communities. Bacterial abundance ranged from 1.5 × 10 5 to 6.7 × 10 6 ml -1 melted sample and viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 50 publications
1
22
0
3
Order By: Relevance
“…Bacterial abundances in the sea ice on the Mackenzie Shelf were within the range previously observed for Antarctic (Gowing et al 2004 and references therein) and Arctic sea ice (Bunch & Harland 1990, Gradinger & Zhang 1997. Bacterial abundances from the ice-water interface were also comparable with previous estimates for surface waters in the same area (Garneau et al 2006).…”
Section: Discussionsupporting
confidence: 77%
“…Bacterial abundances in the sea ice on the Mackenzie Shelf were within the range previously observed for Antarctic (Gowing et al 2004 and references therein) and Arctic sea ice (Bunch & Harland 1990, Gradinger & Zhang 1997. Bacterial abundances from the ice-water interface were also comparable with previous estimates for surface waters in the same area (Garneau et al 2006).…”
Section: Discussionsupporting
confidence: 77%
“…High virus concentrations affecting both eukaryote and prokaryote populations have been reported from the sea-ice habitat (Maranger et al 1994, Borriss et al 2003, Gowing 2003, Gowing et al 2004 and are suggested to significantly affect sea-ice bacterial populations in winter and early spring (Wells & Deming 2006). …”
Section: Actively Respiring Bacteriamentioning
confidence: 99%
“…such as chl a measurements). Our studies of ice communities in the Ross Sea have included the consideration of a range of microbial forms from viruses (Gowing et al 2002, Gowing 2003 and bacteria (Stewart et al 2001, Gowing et al 2004) to protists. Here, we describe the community composition of the ice biota in pack ice regions of the Ross Sea during the autumn to winter transition and during the summer.…”
Section: Introductionmentioning
confidence: 99%